2017
DOI: 10.1111/1462-2920.13614
|View full text |Cite
|
Sign up to set email alerts
|

Two degradation strategies for overcoming the recalcitrance of natural lignocellulosic xylan by polysaccharides‐binding GH10 and GH11 xylanases of filamentous fungi

Abstract: The recalcitrance of lignocellulose forms a strong barrier for the bioconversion of lignocellulosic biomass in chemical or biofuel industries. Filamentous fungi are major plant biomass decomposer, and capable of forming all the required enzymes. Here, they characterized the GH10 and GH11 endo-xylanases and a CE1 acetyl-xylan esterase (Axe1) from a superior biomass-degrading strain, Aspergillus fumigatus Z5, and examined how they interact in xylan degradation. Cellulose-binding (CBM1) domain inhibited GH10 xyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Although we cannot give that the interactions between CBM1/linker and hydrolase domain affected the thermostability of Xyn10A, it’s quite possible. Our previous result (Miao et al 2017 ) showed that remove of CBM1 domain or together with linker region both significantly increased the xylanase activity of Xyn10A, indicating that the interference of CBM1 and linker to hydrolase domain actually existed. When the hydrolase domain is not protected by the linker region, it will be more prone for unfolding by high temperature.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although we cannot give that the interactions between CBM1/linker and hydrolase domain affected the thermostability of Xyn10A, it’s quite possible. Our previous result (Miao et al 2017 ) showed that remove of CBM1 domain or together with linker region both significantly increased the xylanase activity of Xyn10A, indicating that the interference of CBM1 and linker to hydrolase domain actually existed. When the hydrolase domain is not protected by the linker region, it will be more prone for unfolding by high temperature.…”
Section: Discussionmentioning
confidence: 88%
“…CBM1 domain has a function of cellulose-binding (Boraston et al 2004 ). With the help of CBM1, Xyn10A could get close to lignocellulosic biomass and bind the crystalline cellulose inside to degrade xylan around (Miao et al 2017 ). From this aspect, CBM1 domain and linker region should play an important role during the effect on Xyn10A’s stability through the interactions of the basic amino acid chains or 3D structures, and the fact is that removal of CBM1 and linker from Xyn10A do decrease its ability to resist high temperature (> 70 °C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctive relationships between SOC-decomposing enzyme activity and microbial abundance revealed that fungi are more important in recalcitrant-SOC turnover while bacteria are more important in labile-SOC turnover. For instance, fungi are more efficient at decomposing lignocellulose than bacteria [ 60 ]. Moreover, more copiotrophic bacteria contain more labile-SOC-decomposing genes [ 61 ], which promotes labile-SOC turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Logically, the adjustment is to achieve the optimal synergy of extracellular enzymes under different pH conditions, which possibly could be explained from the different enzymatic properties of cellulases and hemicellulases. And, it is really the fact that cellulases and xylanases from the same filamentous fungus have different enzymatic properties, such as thermostability, optimal temperature, specific activity and functional domains [38]. Just like extracellular proteases, they were distinguished as acidic, neutral and alkaline proteases and regulated by the PacC-mediated system [39].…”
Section: Discussionmentioning
confidence: 99%